Comparison of sars-cov-2 rapid tests and formal serological testing on deceased persons in Cape Town Metro - Carlisle, Tayna (Department of Pathology, 2023)
The COVID-19 disease was declared a global pandemic in 2020 and since, it is unclear how many people have truly been infected. Additionally, there is a paucity of research into post mortem antibody testing. An antibody screening tool that is suitable for use in the mortuary setting would go a long way to better document previous COVID-19 infections in deceased persons for surveillance purposes, which would add value to public health systems. This pilot study aimed to explore the use of the Sure Screen COVID- 19 IgG/IgM Rapid Test Cassette in a deceased population, and to compare it to the gold- standard antibody tests in South Africa, to determine the most suitable form of antibody testing for post-mortem samples. Thirty cases, with suspected COVID-19 infection in their lifetime, were recruited from Salt River and Tygerberg mortuaries following informed consent from next-of-kin. Positive COVID-19 PCR (PCP) test confirmation for SARS-CoV-2 was located for 19 of the participants. Blood was collected at autopsy into serum separator tubes which, were found to separate better when centrifuged immediately after sample collection. Sure Screen testing was carried out alongside Roche Diagnostics Elecsys Anti-SARS-CoV-2 and Abbott Architect SARS-CoV-2 IgG Assay. For the confirmed PCP cases, Elecsys' sensitivity was the highest at 94.74%, followed by Sure Screen IgG (78.95%). There was only one case with PCP confirmation with a negative Elecsys result and, in this instance, there was a longer interval between death and autopsy (8 days). No variables relating to time intervals between PCP, death and antibody testing were found to significantly influence the antibody test results. Overall Roche's Elecsys performed the best on our cohort of post-mortem serum samples, followed by Sure Screen, and lastly, Abbott's Architect assay. Based on these results alone, the Sure Screen test demonstrates potential as a screening tool in the mortuary setting, which should be followed up with Roche's Elecsys assay for diagnostic confirmation. However, it is recommended that the sample size be expanded to add weight to this preliminary conclusion.